Social network evolution during long-term migration: a comparison of three case studies in the South Wales region. (2nd January 2017) - Knight, Julie; Thompson, Andrew; Lever, John
ABSTRACT: Ten years after Poland joined the European Union (EU), a sizable number of the once considered short-term migrants that entered the United Kingdom (UK) post-2004 have remained. From the literature, it is known that, when initially migrating, social networks composed of family and friends are used to facilitate migration. Later, migrants' social networks may evolve to include local, non-ethnic members of the community. Through these networks, migrants may access new opportunities within the local economy. They also serve to socialise newcomers in the cultural modalities of life in the destination country. However, what if migrants' social networks do not evolve or evolve in a limited manner? Is cultural integration still possible under these conditions? Using data collected from three case studies in the South Wales region – Cardiff, Merthyr Tydfil and Llanelli – from 2008–2012, the aim of this article is to compare Polish migrants' social network usage, or lack thereof, over time. This comparison will be used to understand how these social networks can be catalysts and barriers for cultural integration. The findings point to the migrants' varied use of their local social networks, which is dependent upon their language skill acquisition and their labour market mobility in the destination country.